2016
DOI: 10.5249/jivr.v9i2.858
|View full text |Cite
|
Sign up to set email alerts
|

Attention deficit/hyperactivity disorder and risk of injuries: a systematic review and meta-analysis

Abstract: Abstract:Background:This study systematically reviewed the literature in order to determine the effect of Attention-Deficit Hyperactivity Disorder (ADHD) on injuries and assessed the magnitude of the potential association.Methods:A systematic review of the studies examining the association of ADHD and injuries was carried out across multiple databases. Odds ratios and standardized mean differences were pooled. Results:A total of 35 studies were selected for quantitative analysis. The association of ADHD and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…A recent epidemiological study confirmed higher mortality rates among ADHD patients, not only because of suicide but also due to other unnatural causes, especially accidents (Dalsgaard, Østergaard, Leckman, Mortensen, & Pedersen, 2015). Other authors detected a higher prevalence of injuries (Amiri, Sadeghi-Bazargani, Nazari, Ranjbar, & Abdi, 2017), vehicle crashes (Vaa, 2014) and bone fractures (Chou, Lin, Sung, & Kao, 2014) among ADHD patients, which seemed to be reverted by pharmacological treatment (Surman, Fried, Rhodewalt, & Boland, 2017).…”
mentioning
confidence: 92%
“…A recent epidemiological study confirmed higher mortality rates among ADHD patients, not only because of suicide but also due to other unnatural causes, especially accidents (Dalsgaard, Østergaard, Leckman, Mortensen, & Pedersen, 2015). Other authors detected a higher prevalence of injuries (Amiri, Sadeghi-Bazargani, Nazari, Ranjbar, & Abdi, 2017), vehicle crashes (Vaa, 2014) and bone fractures (Chou, Lin, Sung, & Kao, 2014) among ADHD patients, which seemed to be reverted by pharmacological treatment (Surman, Fried, Rhodewalt, & Boland, 2017).…”
mentioning
confidence: 92%
“…In a birth cohort study with 6,111 children and adolescents, children at eight years of age presenting hyperactivity symptoms were 1.7 times more likely to have already required hospitalization between the ages of zero to seven [4]. The results of systematic reviews show that children with ADHD are have a significant higher risk of accidents [20, 21]. And also this risk is even higher when only poisonings and intoxications are evaluated [22].…”
Section: Introductionmentioning
confidence: 99%
“…Among the youngest children (1-7 years old) the prevalence is even higher (20.1%) (2). The impact of common mental disorders among children such as ADHD as to major costs for both the individual and the society are wellknown, negatively affecting sick leave, increased mental and physical morbidity, alcohol and substance abuse, crime, relational problems, injuries, and suicide (3)(4)(5)(6)(7)(8)(9). Likewise, for children with anxiety disorders the impact is detrimental as well, with frequent experience of social, peer, and school related problems (10,11).…”
Section: Introductionmentioning
confidence: 99%